2020
DOI: 10.2174/1874467212666190724150723
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase (PTP1B): A promising Drug Target Against Life-threatening Ailments

Abstract: Background: Protein tyrosine phosphatases are enzymes which help in the signal transduction in diabetes, obesity, cancer, liver diseases and neurodegenerative diseases. PTP1B is the main member of this enzyme from the protein extract of human placenta. In phosphate inhibitors development, significant progress has been made over the last 10 years. In early-stage clinical trials, few compounds have reached whereas in the later stage trials or registration, yet none have progressed. Many researchers investigate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…On the other hand, PTP1B serves as a key negative regulator of the tyrosine phosphorylation cascade integral to the leptin and insulin signaling pathway and has been proposed as a therapy to treat type 2 diabetes and obesity. Inhibition of PTP1B may be an attractive target to improve insulin sensitivity in different cell types (Través et al, ) and has potential benefits for the treatment of some diseases, including diabetes, obesity, cancer, liver diseases, and neurodegenerative diseases (Kumar, Rana, Rana, & Bhatia, ). Along this line, a number of diterpenes and their derivatives have been shown to inhibit PTP1B activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PTP1B serves as a key negative regulator of the tyrosine phosphorylation cascade integral to the leptin and insulin signaling pathway and has been proposed as a therapy to treat type 2 diabetes and obesity. Inhibition of PTP1B may be an attractive target to improve insulin sensitivity in different cell types (Través et al, ) and has potential benefits for the treatment of some diseases, including diabetes, obesity, cancer, liver diseases, and neurodegenerative diseases (Kumar, Rana, Rana, & Bhatia, ). Along this line, a number of diterpenes and their derivatives have been shown to inhibit PTP1B activity.…”
Section: Discussionmentioning
confidence: 99%
“…Protein tyrosine phosphatase 1B [PTP1B; encoded by protein tyrosine phosphatase non-receptor type 1 (PTPN1)] is an important member in PTP superfamily of proteins. PTPs catalyze phosphate monoesters hydrolysis on tyrosine residues; they are also known to act as signaling molecules to regulate a number of cellular processes, including cell growth, differentiation, mitotic cycle and oncogenic transformation ( 12 ). To date, PTP1B has been reported to be also involved in the development of obesity, diabetes, cancers and cardiovascular diseases ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the pathological mechanism revealed that DM has a close relation to the protein tyrosine phosphatase (PTP) family, which plays a pivotal role in the regulation of insulin function by dephosphorylating the tyrosine residues of proteins [6]. Among the PTP family, PTP1B is a critical member and is in charge of insulin and leptin signaling pathways, and is a negative regulator of the insulin receptor (IR) signal transduction pathway that leads to insulin resistance, which makes this enzyme a promising therapeutic Molecules 2021, 26, 7433 2 of 16 target to manage DM [7,8]. In insulin signaling, PTP1B is known to dephosphorylate the activated insulin receptor and insulin receptor substrates to attenuate the cellular response to insulin binding [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Among the PTP family, PTP1B is a critical member and is in charge of insulin and leptin signaling pathways, and is a negative regulator of the insulin receptor (IR) signal transduction pathway that leads to insulin resistance, which makes this enzyme a promising therapeutic Molecules 2021, 26, 7433 2 of 16 target to manage DM [7,8]. In insulin signaling, PTP1B is known to dephosphorylate the activated insulin receptor and insulin receptor substrates to attenuate the cellular response to insulin binding [7,9]. Mice with PTP1B gene knockouts have enhanced insulin sensitivity and low body weight, even when fed a high-fat diet [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation